The Role of Critical Laboratory Parameters to Determine the Severity and Prognosis of COVID-19: Systematic Review - Amanda Yuanita Kusdjianto (Cermin Dunia Kedokteran, 2022)
Introduction: Few studies have addressed the diagnostic and prognostic value of abnormal laboratory findings in COVID-19 patients. Objective: To identify and assess published studies on the role of laboratory parameters to determine the severity of COVID-19 patients. Method: Systematic review of articles identified from NCBI, Pubmed, BMC, and Elsevier from 2020-2022. Results: Laboratory parameters: complete blood count, serum electrolyte, renal function, liver function, pancreatic enzymes, D-dimer, inflammatory cytokines, and C-reactive protein have a diagnostic and prognostic value in determining the severity of COVID-19. Conclusion: Laboratory parameters have functional prognostic value in determining COVID-19 severity. Pendahuluan: Beberapa penelitian telah membahas nilai diagnostik dan prognostik dari temuan laboratorium abnormal pada pasien COVID-19.Tujuan: Mengidentifikasi peranan parameter laboratorium dalam menentukan keparahan pasien COVID-19. Metode: Review sistematik atas artikel berasal dari NCBI, Pubmed, BMC, Elsevier tahun 2020-2022. Hasil: Parameter laboratorium darah lengkap, elektrolit serum, fungsi ginjal, hati, pankreas, D-dimer, sitokin inflamasi, dan C-reactive protein memiliki nilai diagnosis dan prognosis pasien COVID-19. Simpulan: Parameter laboratorium berperan dalam menentukan keparahan pasien COVID-19